2024
DOI: 10.1128/spectrum.01050-23
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the gut virome of patients with atherosclerotic cardiovascular disease

Youshan Li,
Jie Ma,
Jinxin Meng
et al.

Abstract: The gut microbiota is an important risk factor and therapeutic target in atherosclerotic cardiovascular disease (ACVD), a leading cause of morbidity and mortality worldwide. However, alterations in the gut viral community and its contribution to ACVD have rarely been investigated. In this study, we characterized and compared the gut viromes from the fecal metagenomes of 214 patients with ACVD and 171 healthy individuals using a reference-dependent virome approach. We revealed that ACVD patients exhibited a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Correlation analysis showed that enterococcus, streptococcus and ruminococcus were widely associated with viral operational taxonomic unit in patients with cardiovascular disease. This also reflects the fact that enteroviruses affect disease by relying on gut bacteria (47). In summary, we found that there may be a complex network among gut microbes, with interactions among bacteria, viruses, and fungi that jointly affect the occurrence and development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Correlation analysis showed that enterococcus, streptococcus and ruminococcus were widely associated with viral operational taxonomic unit in patients with cardiovascular disease. This also reflects the fact that enteroviruses affect disease by relying on gut bacteria (47). In summary, we found that there may be a complex network among gut microbes, with interactions among bacteria, viruses, and fungi that jointly affect the occurrence and development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 53%
“…As far as we know, bacteria are a major component of the gut microbiome, but viruses, fungi, and archaea are also present, they live symbiotic in our gut. Although intestinal flora plays an important role in atherosclerosis, enteroviruses, fungi and their metabolites are also involved in the development of atherosclerosis (46,47). First of all, the gut microbiota of adults is mainly composed of five phyla: Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, and Cerrucomicrobia (48), and changes in the components of these flora can cause ecological imbalance of intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…While bacteria are the primary components of the gut microbiome, other symbionts like viruses, fungi, and archaea also play significant roles. Recent studies ( Chen et al, 2023 ; Li et al, 2024 ) have suggested a link between viruses and the incidence of atherosclerotic diseases, indicating that other components of the human symbiotic microbial system, beyond bacteria, may have associations with PAD that warrant further investigation. Our current analysis focuses solely on the correlation between the gut microbiota and PAD, leaving the relationships between other components of the human symbiotic microbial system and PAD to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Using VLP-based metagenomic sequencing, we enhanced the detection of previously missed viral diversity and species, and shed light on the interplay between gut viruses and bacteria. A notable finding was the increased proportion of Microviridae, which predominantly target Gram-negative bacteria [ 40 ], and has been implicated in various conditions, including IBD, irritable bowel syndrome (IBS), and coronary heart disease [ 41 44 ]. Our results suggested an elevated prevalence of Microviridae in arthritis patients, deviating from typical stool virome.…”
Section: Discussionmentioning
confidence: 99%